Differences between early‐onset pathological gambling and later‐onset pathological gambling: data from the National Epidemiologic Survey on Alcohol and Related Conditions (NESARC). (23rd January 2014) - Verdura Vizcaíno, Ernesto José; Fernández‐Navarro, Pablo; Petry, Nancy; Rubio, Gabriel; Blanco, Carlos
Abstract Aims To examine differences between early‐onset versus later‐onset pathological gamblers in socio‐demographic characteristics, rates of Axis I and II disorders, preferred type of gambling and rates of treatment‐seeking in a large nationally representative survey of adults in the United States. Design Data were collected from face‐to‐face interviews using the Alcohol Use Disorder and Associated Disabilities Interview Schedule DSM‐IV version IV (AUDADIS‐IV). Setting and Measurement The study drew on data from the United States' National Epidemiologic Survey on Alcohol and Related Conditions (NESARC). Participants All individuals with a DSM‐IV diagnosis of pathological gambling (PG). To be consistent with prior studies, age of onset of PG was dichotomized as 25 years and younger (early‐onset) versus 26 years and older (later‐onset). Findings Individuals with early‐onset PG were more likely than individuals with later‐onset PG to be male [odds ratio (OR) = 2.86; 95% confidence interval (CI) = 1.20, 6.82], never married (OR = 3.51; 95% CI = 1.39, 8.84), to have income below US70 000 (OR = 0.09; 95% CI = 0.01, 0.61), to belong to younger cohorts (OR = 0.93; 95% CI = 0.89, 0.97) and to have a cluster B personality disorder (OR = 4.11; 95% CI = 1.77, 9.55), but less likely to have a mood disorder (OR = 0.42; 95% CI = 0.19, 0.94). There were no differences between individuals with early‐ and later‐onset PG regarding rates of treatment‐seeking (OR = 0.71; 95% CI = 0.20, 2.43) or preferred type of gambling (OR = 2.00; 95% CI = 0.55, 7.3). All results remained significant after adjusting for age, sex and race, except the difference in the prevalence for mood disorders, which was no longer significant. Conclusions Individuals with early‐onset versus later‐onset pathological gambling differ in several socio‐demographic and clinical characteristics, but not in their preferred types of game. Individuals from more recent cohorts appear to be at significantly increased risk for developing early‐onset pathological gambling.